Dalla voce alla carta: l’esperienza dei collettivi femministi nelle pagine di «Differenze» - Federica Paoli (Laboratoire Italien)
During the 1970s, a number of magazines linked to the women’s movement were published in Italy, one of the most original of these being Differenze. Published in Rome between 1976 and 1982, it was written in turn by women from different feminist collectives. It was, therefore, a magazine that disseminated the political practices of the different women’s movement groups in the capital. Separatism, autonomy and self-awareness were the three areas of common ground between the different collectives that published the magazine. The idea was, in fact, to give coverage to the differences in feminist practices that in 1976 had become a reality for the movement, differences that at the same time could have been a potential asset and a cause of disintegration. The magazine was created with the ambition of serving as a flexible forum for the exchange of information and documents, and was set up as an instrument that could adapt to the needs of each collective and maintain the typical circularity of discourse in the small feminist group. Twelve issues were printed at irregular intervals, partly reflecting the dynamics of the movement and its different phases. Differenze is now a key historical source for ascertaining the realities that have permeated Roman feminism; it is a wealth of documents and testimonies, and voices whose conversations help to tell the story of Italian feminism.